1999
DOI: 10.1038/sj.ijir.3900394
|View full text |Cite
|
Sign up to set email alerts
|

The penis is not protected — in hypertension there are vascular changes in the penis which are similar to those in other vascular beds

Abstract: In hypertension, small arteries in a variety of vascular beds undergo structural changes that increase resistance. To assess whether there are differential structural changes in the penis that accompany hypertension, we began with determining structurally-based vascular resistance properties in penile and hindlimb vascular beds of adult spontaneously hypertensive rats (SHR) and Sprague-Dawley (SD) rats.In anesthetized SHR, the penile and hindlimb vasculature were isolated and perfused, maximum dilation was ind… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
38
0
3

Year Published

2001
2001
2022
2022

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 51 publications
(46 citation statements)
references
References 26 publications
5
38
0
3
Order By: Relevance
“…25 Hemodynamic studies in SHR species have shown that hypertension in these animals leads to structural changes in penile vasculature similar to those in other vascular beds, characterized by a narrow vascular lumen and increased medial smooth muscle bulk. 26 In addition, these studies imply the loss of functional control mechanisms that protect the penile vasculature from structural changes that may have a negative impact on penile blood flow. 26 Recent in vivo physiological studies in experimental animal models described impairment of erectile response in hypertensive animals.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…25 Hemodynamic studies in SHR species have shown that hypertension in these animals leads to structural changes in penile vasculature similar to those in other vascular beds, characterized by a narrow vascular lumen and increased medial smooth muscle bulk. 26 In addition, these studies imply the loss of functional control mechanisms that protect the penile vasculature from structural changes that may have a negative impact on penile blood flow. 26 Recent in vivo physiological studies in experimental animal models described impairment of erectile response in hypertensive animals.…”
Section: Discussionmentioning
confidence: 99%
“…26 In addition, these studies imply the loss of functional control mechanisms that protect the penile vasculature from structural changes that may have a negative impact on penile blood flow. 26 Recent in vivo physiological studies in experimental animal models described impairment of erectile response in hypertensive animals. Chitaley et al 27 demonstrated a decrement in erectile response in stroke-prone SHR animals.…”
Section: Discussionmentioning
confidence: 99%
“…21 Such increased resistance has been shown to result in structural changes to the penile vasculature, including both arterial and erectile tissues. 22 As we were not able to control for these factors, they may have diluted the association between ED and hyperthyroidism detected in this study. This study supports the conclusions of the two previous studies investigating the association between dysthyroidism and ED.…”
Section: Resultsmentioning
confidence: 77%
“…It is conceivable that these changes may occur also in conditions of chronic hypoxia in men and may lead to alterations in penile structures similar to those already described in other organs (Wespes et al 1998, Okabe et al 1999. These phenomena might contribute to the pathogenesis of erectile dysfunction that frequently complicate atherosclerosis, diabetes mellitus, hypertension, obstructive pulmonary disease and intense cigarette smoking.…”
Section: Discussionmentioning
confidence: 96%